2016
DOI: 10.1007/s00784-016-1966-1
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of multimode adhesives to enamel and dentin after one year of water storage

Abstract: In general, multimode adhesives showed similar behavior when compared to traditional adhesive techniques. Multimode adhesives are one-step self-etching adhesives that can also be used after enamel/dentin phosphoric acid etching, but each product may work better in specific conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 33 publications
4
52
0
3
Order By: Relevance
“…Shear fatigue strength with pre-etching were increased approximately 35% for AU, 36% for CU, 52% for GP, and 58% for SU. Recently reported studies 39,40) have reported that the enamel bond durability of universal adhesives is greater with phosphoric acid preetching than without pre-etching. These findings agree with the present study, although the level of increase in bond fatigue durability of universal adhesives associated with phosphoric acid pre-etching of enamel was material-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Shear fatigue strength with pre-etching were increased approximately 35% for AU, 36% for CU, 52% for GP, and 58% for SU. Recently reported studies 39,40) have reported that the enamel bond durability of universal adhesives is greater with phosphoric acid preetching than without pre-etching. These findings agree with the present study, although the level of increase in bond fatigue durability of universal adhesives associated with phosphoric acid pre-etching of enamel was material-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that the silane-containing Universal adhesive did not seem very effective and stable, and recommended the use of a separate silane primer to achieve enough silane-coupling effect (24). In addition, studies show that multi-mode systems may absorb water even after curing, which degrades the polymer network, reducing the bond strength (15,25). The lack of interaction of SU with Ni-Cr alloy reflects in the failure mode that was 100% adhesive.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that universal adhesives show higher dentin bond strength than two‐step self‐etch adhesives . By contrast, other studies found either no significant difference or that the two‐step self‐etch adhesives was higher than universal adhesives in dentin bond strength . Therefore, the relative dentin bond strength of universal adhesives and two‐step self‐etch adhesives is still a controversial topic and further work is necessary to elucidate differences in the bonding performance of universal adhesives and two‐step self‐etch adhesives.…”
mentioning
confidence: 92%